Detecção de Fotóns Isolados em 1550 nm: Simulação e Resultados Experimentais DOI: 10.14209/jcis.2003.19 - André Pereira Thé, George; Viana Ramos, Rubens (Journal of Communication and Information Systems, 2015)
Quantum key distribution is a new technique that permits secure distribution of a bit string, used as key in cryptographic protocols. The security is guaranteed by suitable coding of the information in a quantum property and from the fact that a quantum cannot be both split and cloned. The present quantum-cryptographic protocols use a quantum (photon in optical systems) to carry the information. Hence, for the construction of an optical set up able to run quantum-cryptographic protocols, it is necessary use single-photon detectors. In this paper, numerical simulations and experimental results of single-photon detectors, in 1550 nm, using avalanche photodiode are shown.